Striking a balance: how long physical activity is ideal for academic success? Based on cognitive and physical fitness mediation analysis - Liu, Guoqing; Li, Wenjie; Li, Xiaotian (Frontiers in Psychology, 2023)
Balancing physical activity and studying is an important issue facing Chinese teenagers. Therefore, numerous studies have found that engaging in physical activity can promote academic performance among students. However, what is the optimal duration of physical activity? This study used data from the China Education Panel Survey, with a sample size of 18,009 valid respondents. General linear regression analysis was conducted using Stata 17 software to evaluate the effects of different durations of physical activity, cognitive ability, and physical Fitness on academic performance among adolescents. Furthermore, the "Bootstrap Mediation" method and the "Maximum Likelihood Estimation" method were used to analyze whether physical health and cognitive ability have significant mediating effects. The present study reveals the following findings: 1) There exists a non-linear relationship between students' academic performance and the duration of physical exercise. The greatest improvement in academic performance is observed when the exercise duration reaches two hours. 2) Physical exercise can enhance students' academic performance by promoting physical health and cognitive abilities. 3) Gender heterogeneity is observed, with the optimal exercise duration for male students being two hours, while female students exhibit the highest academic performance when exercising for one hour. This study provides theoretical guidance for research on adolescents' participation in physical Activity and improving academic performance, enabling adolescents to engage in physical Activity more scientifically and rationally.